Experimental study on ballistic resistance of sandwich panel protection structure with kenaf foam as a core material against small arm bullet - Zainol Abidin, Mohamad Hafiz; Mohamad, Mahmod Abd Hakim; Ahmad Zaidi, Ahmad Mujahid; Wan Mat, Wan Ali (Trans Tech Publications, 2013)
This project is about an experimental impact resistance and behaviour of sandwich panel structure, consists of steel plates and kenaf foam. The use of natural fiber reinforcement foam could give a great advantages in weigh reduction which very useful in military mobility and transportability. A standard rifle was used to launch a small bullet (5.56 mm) in constant velocity towards the sandwich panels. The experiment’s result is based on the depth of the indentation due to the penetration against the armour. The best specimen combining both parameters of study is 20% of kenaf with 45 mm thickness because it can resists the most impact from the bullet. Therefore, it can be concluded that using kenaf to reinforce the polyurethane is success in enhancing its strength and mechanical properties.